Soluble CD40 receptor is a biomarker of the burden of carotid artery atherosclerosis in subjects at high cardiovascular risk. (February 2022) - Leonetti, Simone; Tricò, Domenico; Nesti, Lorenzo; Baldi, Simona; Kozakova, Michaela; Goncalves, Isabel; Nilsson, Jan; Shore, Angela; Khan, Faisel; Natali, Andrea
Abstract: Background and aims: The severity of the atherosclerotic burden is hardly quantifiable in subjects at high cardiovascular (CV) risk under intensive pharmacological therapy. Several molecules have been proposed as circulating biomarkers of atherosclerosis, but none has emerged as clinically meaningful. Methods: Circulating proteins involved in inflammation, plaque remodeling, smooth muscle cell migration, apoptosis and endothelial activity were measured by Proximity Extension Assay in the SUMMIT study cohort (n = 1500), including patients with type 2 diabetes (66%) and established CV disease (50%), who underwent ultrasound assessment of carotid atherosclerosis with total plaque area quantification. Results: In patients with evidence of carotid artery atherosclerosis (n = 1174), seven biomarkers were identified as the more closely related to atherosclerosis extension. Compared with a multivariable model including major traditional CV risk factors, the percentage gain of explained variability in total plaque area was the greatest (33%) after inclusion of CD40 receptor (CD40R) ligand, followed by PDGF (30%), CD40R (26%), EGF (22%), CXCL1 (15%), HBEGF and MMP-17 (both 11%). The relationship of total plaque area with CD40R, PDGF was hyperbolic. In the whole study cohort, including subjects without carotid plaques, CD40R was the strongest predictor of the presence and extension of carotid atherosclerosis. Subjects in the third CD40R tertile had a more than two-fold greater atherosclerotic burden compared with lower CD40R tertiles, despite an only marginally higher load of CV risk factors. Conclusions: CD40R stands among an extended set of plausible atherosclerosis-related biomarkers as the most powerful predictor of carotid atherosclerosis burden in a high CV risk cohort. Graphical abstract: Image 1 Highlights: The extension of atherosclerosis cannot be accurately predicted using clinical variables. This holds true particularly in populations at high/very-high cardiovascular risk. Several circulating proteins have been evaluated, but none proved powerful enough. 19 plausible biomarkers were ranked in terms of strength and predictive power. CD40R emerged as a the most powerful biomarker of carotid atherosclerosis extension.